To determine whether the equation \( 3 - 5 \cdot (81\sqrt{4})^{3-4} = 3 - 6 \) is true or false, we will simplify both sides step by step.
Starting with the left side:
-
Calculate \( \sqrt{4} \): \[ \sqrt{4} = 2 \]
-
Substitute back: \[ 81\sqrt{4} = 81 \cdot 2 = 162 \]
-
Now we have: \[ (81\sqrt{4})^{3 - 4} = (162)^{-1} = \frac{1}{162} \]
-
Substitute this into the left side of the equation: \[ 3 - 5 \cdot \frac{1}{162} \]
-
Calculate \( 5 \cdot \frac{1}{162} \): \[ 5 \cdot \frac{1}{162} = \frac{5}{162} \]
-
Thus, the left side becomes: \[ 3 - \frac{5}{162} \]
To simplify \( 3 - \frac{5}{162} \), write \( 3 \) as a fraction: \[ 3 = \frac{486}{162} \] Now subtract: \[ \frac{486}{162} - \frac{5}{162} = \frac{486 - 5}{162} = \frac{481}{162} \]
Now, let's evaluate the right side: \[ 3 - 6 = -3 \]
So we compare: Left side: \( \frac{481}{162} \) Right side: \( -3 \)
Since \( \frac{481}{162} \neq -3 \), the equation is false.
The correct response is: False. There is an error in calculation using the Quotient Property.